Born to be successful: start-up patenting activity determinants. (18th May 2021) - Leonelli, Simona; Masciarelli, Francesca
Patenting is fundamental to start-up survival and growth. Research indicates that patenting enables start-ups to protect their ideas from competitors, profit from their inventions, and signal their value to stakeholders. Drawing on the resource-based theory, the paper shows that start-ups' patenting activity is related to both external and internal conditions. Relying on a sample consisting of 195 start-ups, located in Italy and France, the market scenario, that is, market dynamism and concentration, is found to affect start-ups' patenting activity. Also, the paper shows that start-ups' age is negatively related to patenting, and that entrepreneur narcissism has different impacts based on its prevailing characteristics: entitlement/exploitativeness is positively related to patenting, grandiose exhibitionism is negatively related to it, while leadership/authority shows no connection with this activity.